Os deuses da África no inferno universal: uma leitura dos cultos de exorcismo das entidades afro-brasileiras ontem e hoje na Igreja Universal do Reino de Deus - Frezarini, Marcelo (2011)
This study investigates the differences among the exorcism worships seen in the first and in the current phases of the Igreja Universal do Reino de Deus. From them, the Church s History is divided in three big periods: the foundation process, the consolidation period and the international expansion period. In the exorcism worships there is a process of demonization of the African-Brazilian entities that the Church calls Devil. The Devil gains space and different roles and becomes milder as the Church institutionalizes. Also, the Church s speech becomes more rational as the audience ascends socially